2009
DOI: 10.4250/jcu.2009.17.4.141
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Primary Cardiac Lymphoma Diagnosed by Percutaneous Endomyocardial Biopsy

Abstract: Primary cardiac lymphoma (PCL) is an extranodal non-Hodgkin's lymphoma exclusively located in the heart and/or pericardium. It is rare in immunocompetent patients and represents 1.3% of primary cardiac tumors and 0.5% of extranodal lymphomas. The clinical behavior is aggressive and the early symptoms are cardiac failure, syncope, arrhythmia, or pericardial effusion. Although echocardiography, computed tomography (CT) scan, magnetic resonance image (MRI) are the mainly used imaging techniques to detect cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 12 publications
1
15
0
1
Order By: Relevance
“…To our knowledge, only 23 cases of PCL in immunocompetent patients have been reported to date (Table I). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] According to these reports, no patient presented with noncardiac lymphomatous localization, but, as in our patient, it was impossible to absolutely exclude noncardiac involvement in the absence of autopsic investiga- Nine of these patients were treated with surgical excision followed by chemotherapy, and 5 of them survived at least 6 months after treatment. No evidence exists concerning the necessity of surgery as an adjunct to chemotherapy in PCL; moreover, in those 9 cases surgery was the final diagnostic step, along with excision as treatment.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, only 23 cases of PCL in immunocompetent patients have been reported to date (Table I). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] According to these reports, no patient presented with noncardiac lymphomatous localization, but, as in our patient, it was impossible to absolutely exclude noncardiac involvement in the absence of autopsic investiga- Nine of these patients were treated with surgical excision followed by chemotherapy, and 5 of them survived at least 6 months after treatment. No evidence exists concerning the necessity of surgery as an adjunct to chemotherapy in PCL; moreover, in those 9 cases surgery was the final diagnostic step, along with excision as treatment.…”
Section: Discussionmentioning
confidence: 97%
“…Chin et al [7] found that treatment with chemotherapy alone resulted in remission in almost 61% of patients, while surgery alone had no effect on outcome. Surgery buys time for chemotherapy to be of therapeutic value.…”
Section: Discussionmentioning
confidence: 99%
“…It typically presents in elderly males and predominantly involves the right-sided cardiac chambers, in particular the right atrium 4. Symptoms depend on the degree of infiltration of the heart and surrounding structures.…”
Section: Discussionmentioning
confidence: 99%